Effect of adjuvants on the amount of air included in droplets generated by spray nozzles - Mota, Alisson A. B. [UNESP] (2013)
The air included in droplets generated by spray nozzles directly int0erferes in transport, deposition and retention of the droplets after its impact on the target. The objective of this study was to analyze the interference of adjuvants in the amount of air included in droplets generated by spray nozzles. The treatments were composed by four spray solutions containing mineral oil, vegetable oil, surfactant and water, and three spray nozzles, two air induction type and one pre-orifice. The air included was calculated by the difference between the volume of spray mix (air plus liquid) and only the liquid, which was made by means of sprayed samples captured in a funnel and collected in a graduated cylinder. The surface tension was estimated by the gravimetric method using a precision scale and a graduated pipette. The surfactant provided the largest percentage of air included in the spray. For the surface tension, the mineral oil and the surfactant had the lowest values. It was concluded that the use of adjuvants had a direct influence on the percentage of air included. In addition, products with greater ability to reduce surface tension and to form homogeneous solutions provided the increase in the percentage of air included in the droplet.